Level of physical activity of students from the police force academy in Bratislava - Gabriel Bujdos; Štefan Adamčák; Michal Marko; Anna Kozaňáková (Pedagogy of Health)
Background and Study Aim. A healthy and active lifestyle is becoming one of the most talked topics amongst people from all over the world. Being more physically active has never been more important than today as both jobs and leisure activities are becoming increasingly sedentary. Humans have moved from being very physically active to being less and less active each year. The aim of our study was to find out the degree of satisfaction and the frequency of performing leisure activities among students of the Police Academy in Bratislava, Slovakia.